Ações pedagógicas e concepções sobre educação ambiental: um estudo de caso - Lôbo, Katiane Oliveira (2013)
Environmental education is a subject that interacts with all disciplines the curriculum and must be present in all content taught. Thus, we can’t see it alone, much less, excluding its importance. From this perspective, and through simple everyday practices, local and global scenarios of pollution can be processed. However, the environmental imbalance will not be reversed through isolated or occasional work, it is necessary that we focus on a specific point of this problem so that thus we can positively contribute to the reversal of the situation. From this point of view, we conducted a descriptive study on environmental education in three schools, two state and one city, located in the town of Maranguape (metropolitan region of Fortaleza - CE), in order to describe and analyze how it has been crafted Environmental Education for teachers of elementary and middle school. We used the methodology proposed by Gil (2005), which proposes the technique of structured questionnaires and field observations by applying a non-probability sample. We also use the case study proposed by Yin (2005). Contextualize the Brazilian education, stressing the importance of school and guide our theoretical assumptions about the prospects for Environmental Education Reigota (2009), Barcelos (2010) and Martinez (2006). To characterize the conceptions of teachers use Lima (2002) in line with the dialogicity of Freire (1985). We have also included other authors as Hammes (2004), Delors (1998), Lomborg (2002) and Thursdays (2008). The results demonstrate the lack of recognition of the importance of the Environmental Education, the limited conceptions of teachers and lack of knowledge of it and of natural resources and biodiversity maranguapense. Making us believe in the need for an appropriation of critical and emancipatory Environmental Education this school to awaken in students environmental problems. Upon completion of the research and, after being certain of our conclusion, we made a booklet illustrated on the Environmental Education and socio-environmental practices could be made by the entire school community, which distribute in schools members of our study.